Performance Improvement of Spaceborne SAR Using Antenna Pattern Synthesis Based on Quantum-Behaved Particle Swarm Optimization - Young-Jin Won; Kyun Ho Lee; Jae-Hyun Lee (International Journal of Antennas and Propagation)
This study improves the performance of a spaceborne synthetic aperture radar (SAR) system using an antenna mask design method and antenna pattern synthesis algorithms for an active phased array SAR system. The SAR antenna is an important component that affects the SAR system performance because it is closely related to the antenna pattern. This study proposes a method for antenna mask design that is based on several previous studies as well as the antenna pattern synthesis algorithm, which is based on quantum-behaved particle swarm optimization (QPSO) for an active phased array SAR system. The performance of the designed antenna masks and synthesized patterns demonstrate that the proposed mask design method and antenna pattern synthesis algorithm based on QPSO can be used to improve the SAR system performance for spaceborne applications.